2019
DOI: 10.3390/molecules24102001
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol, Tyrosol and Derivatives and Their Potential Effects on Human Health

Abstract: The Mediterranean diet and olive oil as its quintessential part are almost synonymous with a healthy way of eating and living nowadays. This kind of diet has been highly appreciated and is widely recognized for being associated with many favorable effects, such as reduced incidence of different chronic diseases and prolonged longevity. Although olive oil polyphenols present a minor fraction in the composition of olive oil, they seem to be of great importance when it comes to the health benefits, and interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
292
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(304 citation statements)
references
References 300 publications
(425 reference statements)
7
292
1
4
Order By: Relevance
“…In this sense, Kendall et al reported that OL diffuses in the stomach and remained stable and intact at the gastric level during digestion being absorbed in the small intestine in healthy young adults [56]. Similarly, several studies have established that OL is stable at the gastric level during digestion, since the bioavailability of its main metabolite HTy is higher [57]. On the contrary, Corona et al determined that OL was absorbed in the colon and degraded by gut microbiota in rat intestinal segment that produces HTy, which expresses biological activity [58].…”
Section: Pharmacokinetics Of Secoiridoids From the Olive Treementioning
confidence: 98%
“…In this sense, Kendall et al reported that OL diffuses in the stomach and remained stable and intact at the gastric level during digestion being absorbed in the small intestine in healthy young adults [56]. Similarly, several studies have established that OL is stable at the gastric level during digestion, since the bioavailability of its main metabolite HTy is higher [57]. On the contrary, Corona et al determined that OL was absorbed in the colon and degraded by gut microbiota in rat intestinal segment that produces HTy, which expresses biological activity [58].…”
Section: Pharmacokinetics Of Secoiridoids From the Olive Treementioning
confidence: 98%
“…A comparable situation occurs with the combined administration of EPA and HT, in which attenuation in HFD-induced steatosis development is achieved, an effect characterized by the additivity of EPA and HT effects that mainly depend on HT [37][38][39][40]. Although HT exerts beneficial outcomes associated with its significant direct free radical scavenging action [73,74] (Figure 3), alternate mechanisms of action involve (i) antioxidant responses via Nrf2 activation [75]; (ii) antisteatotic effects underlying PPAR-α [76] and FGF21 [77] upregulation and ER stress downregulation; [78] (iii) improvement of mitochondrial oxidative function through AMPK/PGC-1α signaling to favor FAO [40,75,79]; and (iv) prevention or resolution of inflammatory processes due to NF-κB deactivation [76,80].…”
Section: Diminution Of Liver Steatosis By Natural Products Co-adminismentioning
confidence: 99%
“…It is noteworthy that in the last years, great interest has been placed on hydroxytyrosol; in fact, this phenolic compound was entitled by the "health claim" from the European Food Safety Authority, reporting that "the consumption of olive oil rich in polyphenols (hydroxytyrosol, 5 mg/day) contributes to the protection of oxidative damage to lipids in blood" [14]. In addition, different studies focusing on hydroxytyrosol demonstrated several in vitro biological activities exerted by this compound, mainly related to the modulation of gene expression together with potential anticancer activities [15,16]. However, the amount and composition of these compounds in both olives and olive oils clearly result from the complex interactions between several factors, namely, genetic factors (cultivar) and pedoclimatic conditions [17].…”
Section: Introductionmentioning
confidence: 99%